Effect of Cigarette Smoking on Outcomes in Patients Undergoing Primary Hip Arthroscopy and Labral Reconstruction: A Propensity-Matched Controlled Study With Minimum 2-Year Follow-up. Issue 2 (24th February 2022) - Jimenez, Andrew E.; Lee, Michael S.; George, Tom; Owens, Jade S.; Maldonado, David R.; Saks, Benjamin R.; Lall, Ajay C.; Domb, Benjamin G.
Background: There is a paucity of literature evaluating the effect of cigarette smoking on outcomes in patients undergoing hip arthroscopy and labral reconstruction. Purpose: (1) To report minimum 2-year patient-reported outcome (PRO) scores for patients who smoke cigarettes and underwent primary hip arthroscopic labral reconstruction and (2) to compare these results with those of a propensity-matched control group of patients who have never smoked. Study Design: Cohort study; Level of evidence, 3. Methods: Data were collected for all patients who underwent primary hip arthroscopy for labral reconstruction between January 2011 and January 2019. Patients were eligible for the study if they indicated that they smoked cigarettes within 1 month of surgery and had minimum 2-year postoperative outcome scores for the modified Harris Hip Score (mHHS), Nonarthritic Hip Score (NAHS), and the visual analog scale (VAS) for pain. The percentage of patients achieving the minimal clinically important difference (MCID) and patient-acceptable symptom state (PASS) was recorded. Rates of revision surgery were also documented. These patients were then propensity matched in a 1:3 ratio to patients who had never smoked (controls) for comparison. Results: A total of 20 patients (20 hips) were included with a mean follow-up of 39.9 ± 13.0 months and mean age of 41.4 ± 10.4 years. These patients demonstrated significant improvement from preoperatively to the minimum 2-year follow-up for mHHS, NAHS, and VAS ( P < .05). They also achieved MCID for mHHS and VAS at acceptable rates, 70% for both. When outcomes were compared with those of 60 control patients (60 hips), patients who smoke demonstrated lower preoperative PRO scores but similar minimum 2-year postoperative PRO scores for mHHS and NAHS. Patients who smoke demonstrated lower rates of achieving PASS for mHHS (55% vs 75%) and NAHS (40% vs 61.7%) compared with controls; however, these findings were not statistically significant. Rates of secondary surgery were statistically significantly higher in the smoking group compared with controls (25% vs 5%; P = .031). Survivorship for the smoking patients was 80% and 98.3% for the control group. At the two-year mark survivorship was 90% for the smoking group and 100% for the control group ( P = .06) Conclusion: While smokers can still derive significant improvement from hip arthroscopy, their ultimate functional outcome and rate of secondary surgeries are inferior to those of nonsmokers. As smoking is a significant and modifiable risk factor, we should continue to counsel smokers on smoking cessation prior to and after surgery